Planning of LTE-Apro Network using Licensed Assisted Access combining Spectrum Licensed 1800MHz and Unlicensed 5GHz - Mubarok, Arif; Usman, Uke Kurniawan; Fitrianto, Galih Purnomo (International Journal of Advanced Science Computing and Engineering, 2019)
The number of activities in the room results in an increase in the amount of traffic which means a large surge in cellular users. As large data traffic increases, limited spectrum is available and high spectrum costs, wireless service providers respond by making adjustments to LTE technology. With the presence of LTE-AP supported by an unlicensed spectrum, Telkomsel operators can enjoy the unlicensed spectrum to increase capacity and throughput. Cellular network planning uses 2 scenarios to get the best solution, Scenario 1 is planning the LTE Network with a bandwidth of 20 MHz in band 3 and using a 4x4 MIMO antenna. , scenario 2 planning the LTEAdvanced Pro network uses the LAA method by combining the unlicensed 20 MHz spectrum in band 36 and a licensed 20 MHz sprectrum in band 3 and using a 2x2 MIMO antenna. analysis and simulation using U-Net V500 software. The results of the LTE network planning simulation obtained the average value of RSRP 77 -77.71 dBm, SINR ≥ 11.88 dB, Throughput ≥ 37.079 Mbps and User connected = 98.00%, while the LTE-AP average value of RSRP ≥ -73.51 dBm, SINR ≥ 17.02 dB , Throughput ≥ 49,739 Mbps and User connected = 100.00%. Based on the simulation results, the LTE-AP network planning is very good to be implemented in the city of Bandung, the best solution choice to overcome the limitations of Telkomsel spectrum with the network performance that is very good in terms of coverage and capacity.